Path creation, global production networks and regional development: A comparative international analysis of the offshore wind sector. (May 2019) - MacKinnon, Danny; Dawley, Stuart; Steen, Markus; Menzel, Max-Peter; Karlsen, Asbjørn; Sommer, Pascal; Hansen, Gard Hopsdal; Normann, Håkon Endresen
Highlights: Paper highlights the role of wider extra-regional factors in regional path creation. Develops an analytical framework based on the interplay between four factors. Adopts an international comparative approach, covering Germany, the UK and Norway. Outlines the qualitative characteristics of the paths created. Emphasises the role of national states in the strategic coupling process. Abstract: The question of how regions and nations develop new sources of industrial growth is of recurring interest in economic geography and planning studies. From an evolutionary economic geography (EEG) perspective, new growth paths emerge out of existing economic activities and their associated assets and conditions. In response to the micro-economic and endogenous focus of much EEG research, this paper utilises a broader evolutionary perspective on path creation which stresses the dynamic interplay between four sets of factors: regional assets; key economic and organisational actors; mechanisms of path creation; and multi-scalar institutional environments and policy initiatives. Reflecting the importance of extra-regional networks and institutions, this framework is also informed by the Global Production Networks (GPN) approach, which highlights the process of strategic coupling between firms and regions and its political and institutional mediation by state institutions at different spatial scales. We deploy this framework to investigate regional path creation in the context of renewable energy technologies, focusing specifically on the offshore wind industry. We adopt a comparative cross-national approach, examining the evolution of offshore wind in Germany, the UK and Norway. Of the three cases, Germany has developed the most deep-rooted and holistic path to date, characterised by leading roles in both deployment and manufacturing. By contrast, path creation in the UK and Norway has evolved in more partial and selective ways. The UK's growth path is developing in a relatively shallow manner, based largely upon deployment and 'outside in' investment, whilst Norway's path is emerging in an exogenous, 'inside-out' fashion around a fairly confined set of actors and deployment and supply functions. In conclusion, the paper emphasises the important role of national states in orchestrating the strategic coupling of regional and national assets to particular mechanisms of path creation.